Essays on life writing : from genre to critical practice - Kadar, Marlene, 1950- (Theory/culture series, 1992)
Life writing is the most flexible and open term available for autobiographical fragments and other kinds of autobiographical-seeming texts. It includes the conventional genres of autobiography, journals, memoirs, letters, testimonies, and metafiction, and in earlier definitions it included biography. It is a way of seeing literary and other texts that neither objectifies nor subjectifies the nature of a particular cultural truth. Marlene Kadar has brought together an interdisciplinary and comparative collection of critical and theoretical essays by diverse Canadian scholars, most of whom are women engaged in larger projects in life writing or in archival research. In the more practical pieces the author has discerned a pattern in autobiographical text, or subtext, that has come to revolutionize the life, the critic's approach, or the discipline itself. In the theoretical pieces, authors make cogent proposals to view a body of literature in a new way, often in order to incorporate feminist visions or humanistic interpretations. The contributors represent a broad range of scholars from disciplines within the humanities and beyond. Collectively they provide an impressive overview of a growing field of scholarship.